You Got to Tell: Private Spaces and Public Narrators in Grace Paley’s Stories - Diana Ortega Martín (Literatura: Teoría, Historia, Crítica)
The American storyteller Grace Paley (December 11, 1922-August 22, 2007) has been known for her political activism and her ability to construct powerful voices which recollected female, migrant, and urban collective experiences in post-World War II America. In her stories, Paley emphasizes the act of storytelling as a tool for creating a collective shared experience out of individual characters, making the personal and domestic collective and political. In this paper, I will analyze the role of Paley’s most prominent narrator, Faith Darwin, bridging the gap between the private and public urban spheres in three different and evolutive stories: “A Conversation with My Father” (1972), “The Long-Distance Runner” and “Faith in a Tree” (1974). These stories exemplify how Faith uses different strategies in storytelling with the purpose of achieving personal identity and empowerment through communal identification and the recollection of familiar experiences